Ukrainian Online Marriages and Their Recognition in neighbouring Poland - Wysocka-Bar, Anna; Kernychna, Sofiya (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
The first part of the article analyses the legal regulation of online marriage registration in Ukraine within the context of public service digitalisation and martial law. It examines the development of the Diia-based online marriage registration mechanism and demonstrates that despite procedural digitalisation the legal nature of marriage remains unchanged as it continues to require mandatory State registration. The study highlights the practical advantages of online marriage registration such as increased accessibility, administrative efficiency, transparency, and enhanced security. The second part of the article comments on legal aspects related to the recognition of Ukrainian online marriages in neighbouring Poland. The possibility of transcription of Ukrainian marriage certificate into Polish civil status register is explored in order to find out that public policy clause should not be invoked in this case. Additionally, a theoretical possibility of the recognition through conflict of law rules is explored.